Environment-friendly and biodegradable a-Fe2O3/C20H38O11nanocomposite growth to lengthen the Solanum lycopersicum storage process. (1st June 2022) - Guleria, Geetika; Thakur, Sapna; Sharma, Dhananjay K; Thakur, Shweta; Kumari, Poonam; Shandilya, Mamta
Abstract: In this work, the growth of enviro-friendly and biodegradable α -Fe2 O3 /C20 H38 O11 nanocomposite is reported by means of a real time application to prolong the storage life of Tomato ( Solanum Lycopersicum ). A low temperature technique is used to prepare the α -Fe2 O3  nanoparticles to obtain a crystalline nanopowder. XRD confirms the phase formation and crystalline nature of α -Fe2 O3  nanoparticles. The surface morphology and elemental analysis of α -Fe2 O3 /C20 H38 O11  nanocomposite is conducted by SEM and EDX. Nanocomposite exhibits excellent antimicrobial activity against  Klebsiella pneumoniae  and  Staphylococcus aureus  bacteria. Tomato fruit samples are coated with two different concentrations of α -Fe2 O3 /C20 H38 O11  nanocomposite with 5% UC1A, UC2A and 3% UC1B, UC2B; and uncoated samples UC1, UC2 are stored at room temperature (25 ± 2 °C) and refrigerator temperature (4  °C) respectively for ascorbic acid (vitamin C) analysis on days 0, 4, 8, 12 and 16. Our study revealed that a 3% concentration of α -Fe2 O3 /C20 H38 O11  nanocomposite material is quite potent in maintaining quality aspects of the tomato fruit with no decline in vitamin C under refrigerated conditions up to the 16th day. FTIR analysis of all samples was done to determine the functional groups present in tomato samples after storage. Atomic absorption spectrometer (AAS) was used to analyse the content of Fe in tomato samples.